Transformation of Andragogic Approach in the Formation of Islamic Character of Elementary School Students: An Experimental Study Based on Local Wisdom - Anniez Rachmawati Musslifah; Faqih Purnomosidi; Mirawati Mirawati; Basir Jarah Anilon (Tafkir: Interdisciplinary Journal of Islamic Education, 2026)
The purpose of the research is to analyze the effectiveness of modified andragogic models in fostering Islamic character that is integrated with local wisdom values. The method used was a quasi-experiment with a pretest-posttest control group design, involving 60 students from two Islamic boarding schools as a sample. Data were collected through participatory observation, standardized character scales, and curriculum document analysis. The results showed a significant increase in the aspects of responsibility (p=0.003) and cooperation (p=0.012) compared to the control group, with the greatest effect seen in the internalization of the value of "tepa slira" (tolerance) as a key mediator. The unique findings reveal that the adaptation of the principles of self-directed learning in andragogics can be effective in children when combined with a narrative approach based on folklore. This study not only extends the application of andragogic theory to primary education, but also offers a new conceptual framework, "Andragogy for Children Islamic Character (ACIC)" that is relevant to the context of Islamic education in Indonesia. The practical implications include recommendations for character learning modules based on local wisdom.